2014
DOI: 10.2495/st140011
|View full text |Cite
|
Sign up to set email alerts
|

Do sustainability-experienced travellers prefer a more rational communication of the sustainability of a tourism product?

Abstract: This study empirically examines, in four countries, which communication style (emotional or rational) is most appropriate for addressing sustainabilityexperienced travellers. There are only small differences compared to the average tourist. Rational communication elements, which explain the sustainability of the product, become more important for this specific customer group. However, most emotional communication elements are still more important in most countries, indicating that experienced tourists also pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…We may deduce that event planners could use more emotional communication strategies for this visitor group. Other research has shown that emotional appeals are appropriate for audiences which are not sustainability-minded per se (e.g., Reference [43]), whilst informational appeals are more appealing to sustainability-conscious visitors (e.g., Reference [44]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We may deduce that event planners could use more emotional communication strategies for this visitor group. Other research has shown that emotional appeals are appropriate for audiences which are not sustainability-minded per se (e.g., Reference [43]), whilst informational appeals are more appealing to sustainability-conscious visitors (e.g., Reference [44]).…”
Section: Discussionmentioning
confidence: 99%
“…Future surveys at the SLF may replicate and extend our research design by including other languages. As far as the event's communication strategy is concerned, the literature suggests that emotional appeal techniques are more likely to attract customers who are not primarily motivated to buy sustainably in a tourism context (e.g., Reference [44]). However, the way in which sustainability messages need to be designed in an event context to attract different visitor groups, and especially those who do not yet show any sustainability behaviors but are on the verge of considering behavioral change, has still to be researched.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why in our data we find that accommodation businesses choose to downplay such saliency by not bringing it to the customers' attention or requiring action. Messages would be more appealing if they required no effort from consumers, as opposed to transmitting rational, more cognitively-demanding information (Wehrli et al, 2013). Messages could also be more persuasive by empowering customers in the learning process of sustainability practices through actively experiencing the benefits of such practices (Kachel and Jennings, 2010;Cialdini and Goldstein, 2004), or by using 'descriptive norms' to influence behavior by drawing on a sense of belonging and social acceptance (Goldstein et al, 2008;Han and Kim, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A message like "5.5% reduction in energy use in 2015" is logical, while "Our 5.5% reduction in energy usage in 2015 makes us feel proud and motivates us to keep working" is appealing. Logical or rational sustainability messages are more important for travelers that claim to be experienced in sustainable travel than for those that are not, but overall most travelers prefer emotional messages (Wehrli et al, 2013).…”
Section: Message Contentmentioning
confidence: 99%
“…As a matter of fact, consumer behavior shows trends towards the consumption of green brands and sustainability, as these factors are important when booking their holiday destinations [20,[61][62][63][64]. For this reason, as Edgel [65] recognizes, destinations try to respond to these new demands and show a greater concern to develop more sustainable tourism.…”
Section: What Does It Mean To Be a "Sustainable Tourist"?mentioning
confidence: 99%